The Impact of Television as a Media Institution in Reinforcing and Directing Child Behaviors: A Critical Vision from a Media-Sociological Perspective - asaidani, salami (Journal of Social Sciences and Humanities, 2016)
In recent years, television viewing habits among children have faced significant criticism. Research has demonstrated a correlation between children's television exposure and several ailments, most notably: reduced attention span, obesity, sleep disorders, hypertension, autism-like symptoms, aggression, speech delays, and social withdrawal. Undoubtedly, none of us wish for television to negatively impact our children; however, we must ask ourselves: what exactly are our children watching?"